PENINGKATAN HASIL BELAJAR KETERAMPILAN ANYAMAN PITA DENGAN METODE PEMBELAJARAN KERJA KELOMPOK - RASIMAH, Dra. Ernis, M.Pd, Drs. Abd. Hafiz,M.Pd (Serupa The Journal of Art Education, 2014)
This study aims to improve student learning outcomes inmaking wicker is by using group work method. This type research is aclassroom action research, conducted in semester from January toJune 2014 VII.1 SMP N 7 Lubuk Basung with a total of 25 people inthe learning material made of woven. From the research data obtainedan increase in student learning outcomes are visible from the firstcycle and cycle II. To capability observed that the practice of learningoutcomes woven tape on the first cycle is the average 68. While in thesecond cycle results woven ribbon practice skills using group work anaverage of 80.36. So, practice skills woven ribbon using group workin the classroom learning VII.1 SMP N 7 Lubuk cone successfully andcan improve student learning outcomes.Keywords: Learning outcomes, skills, woven tape, learning, groupwork